Noise Spectroscopy: A Tool to Understand the Physics of Solar Cells - Giovanni Landi; Sergio Pagano; Heinz Christoph Neitzert; Costantino Mauro; Carlo Barone (Energies, 2023)
Noise spectroscopy is essentially focused on the investigation of electric fluctuations produced by physical mechanisms intrinsic to conductor materials. Very complex electrical transport phenomena can be interpreted through the study of the fluctuation properties, which provide interesting information both from the point of view of basic research and of applications. In this respect, low-frequency electric noise analysis was proposed more than twenty years ago to determine the quality of solar cells and photovoltaic modules, and, more recently, for the reliability estimation of heterojunction solar cells. This spectroscopic tool is able to unravel specific aspects related to radiation damage. Moreover, it can be used for a detailed temperature-dependent electrical characterization of the charge carrier capture/emission and recombination kinetics. This gives the possibility to directly evaluate the system health state. Real-time monitoring of the intrinsic noise response is also very important for the identification of the microscopic sources of fluctuations and their dynamic processes. This allows for identifying possible strategies to improve efficiency and performance, especially for emerging photovoltaic devices. In this work are the reported results of detailed electrical transport and noise characterizations referring to three different types of solar cells (silicon-based, organic, and perovskite-based) and they are interpreted in terms of specific physical models.